Cumulative risk of compromised physical, mental and social health in adulthood due to family conflict and financial strain during childhood: a retrospective analysis based on survey data representative of 19 European countries. Issue 3 (29th March 2021) - Santini, Ziggi Ivan; Koyanagi, Ai; Stewart-Brown, Sarah; Perry, Bruce D; Marmot, Michael; Koushede, Vibeke
Abstract : Background: Childhood adversity (CA) has previously been linked to various health problems in adulthood. Investigations into the differential impact of distinct types of CA on a wide range of outcomes are scarce. This study aimed to assess the impact of self-reported childhood family conflict and/or financial strain on health and social functioning in adulthood among Europeans, while taking into account the mediating role of adulthood socioeconomic disadvantage (SED) in these associations. Methods: Using the European Social Survey (ESS) collected in 2014, nationally representative cross-sectional data from 35 475 participants aged 15 years and older in 19 European countries were analysed. Logistic regressions were conducted to assess associations of retrospectively reported family conflict and/or financial strain in childhood with physical and mental health as well as health behaviours and social functioning in adulthood. Results: A quarter of the European population reported having experienced family conflict, financial strain or both in childhood. Financial strain was reported more among older age groups and conflict more among younger age groups. A dose-response pattern with increased risk was demonstrated for almost all physical, behavioral, mental and social outcomes for these aspects of CA compared with no CA, with the highest risk observed in those who experienced both financial strain and family conflict. Adulthood SED mediated a significant proportion of the associations with financial strain (ranging from 5.4% to 72.4%), but did not mediate the associations with conflict. Conclusion: Individuals reporting family conflict or financial strain during childhood are at increased risk of developing a wide range of health and social problems. Those who report financial strain in childhood are more likely to experience SED in adulthood, which in turn increases their risk of experiencing health and social problems. Reported family conflict during childhood conferred increased risk of health and social problems, but adulthood SED did not appear to operate as an indirect pathway.